Flywheel squats versus free weight high load squats for improving high velocity movements in football. A randomized controlled trial - Edvard H. Sagelv; Sigurd Pedersen; Lars Petter R. Nilsen; Andrea Casolo; Boye Welde; Morten B. Randers; Svein Arne Pettersen (BMC, 2020)
Abstract Background High load (HL: > 85% of one repetition maximum (1RM)) squats with maximal intended velocity contractions (MIVC) combined with football sessions can be considered a relevant and time-efficient practice for maintaining and improving high velocity movements in football. Flywheel (FW) resistance exercise (RE) have recently emerged with promising results on physical parameters associated with football performance. Methods In this randomized controlled trial over 6 weeks, 38 recreationally active male football players randomly performed RE with MIVCs two times per week as either 1) FW squats (n = 13) or 2) barbell free weight (BFW) HL squats (n = 13), where a third group served as controls (n = 12). All three groups conducted 2-3 football sessions and one friendly match a week during the intervention period. Pre- to post changes in 10-m sprint, countermovement jump (CMJ) and 1RM partial squat were assessed with univariate analyses of variance. Results The FW and BFW group equally improved their 10-m sprint time (2 and 2%, respectively, within group: both p < 0.001) and jump height (9 and 8%, respectively, within group: both p < 0.001), which was superior to the control group's change (between groups: both p < 0.001). The BFW group experienced a larger increase (46%) in maximal squat strength than the FW group (17%, between groups: p < 0.001), which both were higher than the control group's change (both p < 0.001). Conclusion Squats carried out with FWs or BFWs where both are performed with MIVCs and combined with football sessions, were equally effective in improving sprint time and jump height in football players. The BFW group experienced a more than two-fold larger increase in maximal partial squat strength than the FW group in maximal partial squat strength. This presents FW RE as an alternative to BFW HL RE for improving high velocity movements in football. Trial registration ClinicalTrials.gov Identifier: NCT04113031 (retrospectively registered, date: 02.10.2019).